Historic Community Preservation: The Approach Suitable to Thai Context - Supoj Prompayuk; Panayu Chairatananonda (My University, 2017)
Historic community is actually a kind of cultural heritages. However, in Thailand, a phenomenon contradicting such idea is often found. Namely, tangible heritages, such as residences, buildings or architectural features are well preserved, while intangible heritages, such as social, economic and cultural structure and traditional way of life are widely changed as a result of rising economic opportunities. This phenomenon emerges after a community becomes a historic community which is a way to raise the economic values in locality. Consequently, the other values of the historic community are diminished or faded away. However, there are Thai communities which can preserve the original conditions and maintain their value as a historic community. Hence, this research aims to find the preservation approach and supporting factors in those communities. It is found that those communities raise awareness of local inhabitants and attract them to participate in the preservation in the direction which they want the community to be. As a result, this preservation becomes more sustainable.
Keywords: Phenomenon; Value (mathematics); Local Community; Cultural Heritage Management and Preservation